2003
DOI: 10.1029/2001jc001013
|View full text |Cite
|
Sign up to set email alerts
|

Surface salinity budget in oceanic simulation using data from TOGA COARE

Abstract: [1] A three-dimensional regional model is used to investigate the role of different terms of the salinity budget in the western Pacific during TOGA COARE. The model is a version of the ocean general circulation model (OGCM) developed at the Laboratoire d'Océanographie Dynamique et de Climatologie (LODYC) in Paris and includes open lateral boundaries and a 1.5-level-order turbulence closure scheme. The surface atmospheric forcing used, including water flux, comes from a combination of European Center for Medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It is recognized, however, that the fine vertical salinity structure observed in the western Pacific (Lukas and Lindstrom 1991;Weller and Anderson 1996) is undoubtedly important for the evolution and variability of the mixed layer through, for example, the presence of salinity-stratified barrier layers (Vialard and Delecluse 1998). The spatial heterogeneity of precipitation and the role of advection in such processes (Lukas and Lindstrom 1991;Dourado and Caniaux 2003) mean that the present 1D vertical model is an inappropriate tool for the study of salinity in the mixed layer in the warm pool. The results of such an investigation would most likely impose greater requirements on the vertical resolution throughout the mixed layer, rather than just that of the uppermost layer as suggested by this study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is recognized, however, that the fine vertical salinity structure observed in the western Pacific (Lukas and Lindstrom 1991;Weller and Anderson 1996) is undoubtedly important for the evolution and variability of the mixed layer through, for example, the presence of salinity-stratified barrier layers (Vialard and Delecluse 1998). The spatial heterogeneity of precipitation and the role of advection in such processes (Lukas and Lindstrom 1991;Dourado and Caniaux 2003) mean that the present 1D vertical model is an inappropriate tool for the study of salinity in the mixed layer in the warm pool. The results of such an investigation would most likely impose greater requirements on the vertical resolution throughout the mixed layer, rather than just that of the uppermost layer as suggested by this study.…”
Section: Discussionmentioning
confidence: 95%
“…However, the IMET buoy has fewer salinity sensors than temperature sensors, making it difficult to quantify the effects of salinity on the evolution of the mixed layer. In addition, the spatial heterogeneity of the precipitation field combined with the fact that advection is a significant term of the warm pool salinity budget (Dourado and Caniaux 2003;Feng et al 2000) has meant that only the thermal evolution of the mixed layer has been addressed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…In a realistic mesoscale simulation of the north‐east Atlantic, Caniaux and Planton [] estimated horizontal diffusion of the order of 3% of the mixed layer heat budget. In a mesoscale simulation of the tropical Pacific during the TOGA/COARE experiment, Dourado and Caniaux [] found that horizontal diffusion represented a cooling less than 2 W m −2 or 2% of a heat storage term. Other heat balance studies, performed from data in the same basin and during the same experiment found this term negligible compared to the other mixed layer processes [ Cronin and McPhaden , ; Smyth et al ., ; Feng et al ., ].…”
Section: Data Used and Forcingsmentioning
confidence: 99%
“…In the determination of the conservation of salt in the surface mixed layer, E and P are important parameters that are incorporated in the mathematical expressions of the salinity budget [ Delcroix and Henin , 1991; Foltz and McPhaden , 2008]. The magnitude of variability in E and P especially, and that of other salinity tendency terms such as mixing, vertical and horizontal diffusions, may, however, not lead to an analogous magnitude in variability of salt transport as the processes affecting the tendency terms vary in time and space [ Dourado and Caniaux , 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Many such studies have relied heavily on numerical simulations, which sometimes suffer especially from the estimation of freshwater flux terms [ Murtugudde and Busalacchi , 1998]. This has been explained as arising from the fact that the spatial distribution of atmospheric input functions is non‐Gaussian [ Tomczak , 1995; Dourado and Caniaux , 2003]. Other challenges have been the poor representation of coastal currents and the dominance of Ekman drift over geostrophy in the western coast of India that leads to differences between observed and modeled SSS [ Prasad and Ikeda , 2002b].…”
Section: Introductionmentioning
confidence: 99%